2011
DOI: 10.1212/wnl.0b013e31822c9135
|View full text |Cite
|
Sign up to set email alerts
|

IV thrombolysis and statins

Abstract: In stroke patients receiving IVT, prior statin use was neither an independent predictor of functional outcome nor ICH. It may be considered as an indicator of baseline characteristics that are associated with a less favorable course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
90
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 27 publications
9
90
3
1
Order By: Relevance
“…13,14 Local study investigators completed the forms systematically using prospectively ascertained in-hospital IV ischemic stroke thrombolysis registries. Completed forms from all centers were compiled in the coordinating center Basel, where the analysis of the pooled data was performed, as described previously.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Local study investigators completed the forms systematically using prospectively ascertained in-hospital IV ischemic stroke thrombolysis registries. Completed forms from all centers were compiled in the coordinating center Basel, where the analysis of the pooled data was performed, as described previously.…”
mentioning
confidence: 99%
“…Completed forms from all centers were compiled in the coordinating center Basel, where the analysis of the pooled data was performed, as described previously. 13,14 The following prospectively ascertained variables were used: age, sex, initial stroke severity as assessed using the NIH Stroke Scale (NIHSS), 15 blood pressure before IVT, onset to treatment, initial serum creatinine (SCr) and glucose values in blood serum, etiology according to the TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria, 16 and vascular risk factors according to predefined criteria. 17 Post hoc, we added prior treatment with antithrombotic agents (antiplatelet agents and anticoagulants).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Two large observational studies reported that previous treatment with statin was not an independent predictor of functional outcome or of ICH. 13,14 The aim of the THRombolysis and STatins (THRaST) study was to assess the impact of statin use in the acute phase of ischemic stroke on clinical outcome in patients treated with IV thrombolysis.Authors' affiliations are listed at the end of the article. Go to Neurology.org for full disclosures.…”
mentioning
confidence: 99%
“…The long-term efficacy endpoints were favorable functional outcome (mRS # 2) 16 and excellent functional outcome (mRS # 1) 13 at 3 months. The short-term safety endpoints were neurologic deterioration (NIHSS $4 points from baseline or death) 19 at 7 days and sICH (local or remote parenchymal hematoma type 2 on the imaging scan obtained 22 to 36 hours after treatment, with NIHSS score increase of $4 points from baseline or the lowest value in the first 24 hours or leading to death).…”
mentioning
confidence: 99%